A STATE-OF-THE-ART: AN OPTIMAL PATH ALGORITHM FOR MOBILE AD HOC NETWORK (MANET) AND WIRELESS AD HOC NETWORK (WANET) - Nagaraju, Regonda; Patra, P. Santosh Kumar; Srujana, B.; Ghuge, Priya Aniket (International Journal of Psychosocial Rehabilitation, 2020)
This paper deals with different evolutionary methods, provided to fix the best optimized routes for data communication for peer to peer in mobile communication networks. This differential approach for global multi-objective network simulation, in regards to perform with publishing the prime affordable path in mobile networks. This prototype holds the affordable cost to go for the minimal cost for the path. We studied the way of minimizing a grand total of all convex objective functions, where the attributes of the objective functions are available to different nodes of a cellular network and the cellular nodes are allowed to only communicate with their nearest neighbors. The multiobjective optimization algorithm is applied as a diagnosis toolfor checksum based encryption indata transmission.In the end test results passed by proposed algorithm fulfills the genuineness, in regards to traditional algorithms such as Particle Swarm Optimization and Genetic Algorithm.